Basque adjectival participles: Stative, resultative or experiential - Berro, Ane (Glossa (London), 2019)
In this paper, I analyze the form and meaning of adjectival participles in Basque, an ergative language with a predominant use of analytic verbal forms. I show that even though adjectival participles have similar morphological makeup, they can be the exponents of different aspectual configurations, with different interpretation and syntactic distribution. As attested for other languages such as English and Greek, Basque adjectival participles can be interpreted as stative or resultative (Embick 2004), and also as target state participles or resultant state participles (Kratzer 2000; Anagnostopoulou 2003). As noted in the literature (Anagnostopoulou 2003; Alexiadou & Anagnostopoulou 2008; Alexiadou et al. 2014; Alexiadou et al. 2015), these types are subject to different syntactic distribution, particularly regarding the acceptability of different sorts of event-related and subject-oriented modifiers. In this paper, I propose that a further aspectual class must be included into the typology of adjectival participles: experientials. In fact, adjectival participles in Basque can be interpreted experientially under certain conditions. The five-way typology of participles emerges as the result of the combination of two different aspectual heads (a stativizing Asp head, as in Kratzer 2000 and Embick 2004, and an aspectual operator with anteriority semantics, as in Kratzer 2000; Alexiadou et al. 2014; Alexiadou et al. 2015) with complements of different sizes and nature. In particular, the experiential reading arises when the Asp head of anteriority combines with particular vP semantics and/or with a particular linking relation between the subject of predication and the arguments within VOICEP.